Kondisi Terumbu Karang dengan Indikator Ikan Chaetodontidae di Pulau Sambangan Kepulauan Karimun Jawa, Jepara, Jawa Tengah. - Suryanti Suryanti; Supriharyono Supriharyono; Willy Indrawan (Universitas Diponegoro, 2011)
Abstract Coral reefs are marine ecosystems in tropical marine life constructed by the producer of lime in particular species of stony corals and calcareous algae, together with the biota that live in the bottom of which is a types of molluscs, crustaceans, echinoderms, Polychaeta, Sponge and tunicates and marine biota others are living freely in the surrounding waters. Chaetodontidae or butterfly fish is ordinary reef fish while the distribution in surround coral reef only. The experts agreed on placing fish leadership as